Efficiency enhancement of pyridinium ylide dye-sensitized solar cells by introduction of benzothiadiazolyl chromophore: A computational study. (March 2020) - Li, Zhen-Jiang; Wang, Xue-Hua; Tian, Wen-Li; Huang, Tian-Qi; Meng, A-Lan; Yang, Li-Na
Graphical abstract: Highlights: The intrinsic sensitization mechanism of pyridinium ylide dyes is theoretically investigated. The diethylmalonate anchor is favorable in interfacial charge transfer, anti-aggregation, and long-term stability. The good light harvesting and slow charge recombination suggest a superior efficiency of benzothiadiazole containing film. Abstract: Organic pyridinium ylide sensitizers NO108-NO111 with different anchoring groups show attractive applications in dye-sensitized solar cells. To elucidate the intrinsic sensitization mechanism of this series of dyes, theoretical calculations of electrochemical and spectroscopic properties for free and adsorbed ylides have been performed. Moreover, to prescreen and optimize suitable candidates for pyridinium ylide cells, the benzothiadiazole (BTD) group is introduced in the best-performing ylide NO111, and the afforded dye is coded as NO111-1. Comparing pyiridine- N -oxide in NO108, diethylmalonate in NO111 shows superior properties in terms of interfacial charge transfer, anti-aggregation, and long-term stability. It also demonstrates that the novel designed NO111-1-sensitized film possesses higher average theoretical maximum limit of short-circuit photocurrent density ( J SC max ≈ 23 mA/cm 2 ), and slower parasitic recombination than NO111 one. This result is expected to further reveal the effects of anchoring groups on properties of dyes, and is helpful for the design of more efficient pyridinium ylide dyes.